Three dosimetry models of lipoma arborescens treated by 90Y synovectomy. Issue 5 (9th April 2014) - O'Doherty, Jim; Clauss, Ralf; Scuffham, James; Khan, Aman; Petitguillaume, Alice; Desbrée, Aurélie
Abstract : Purpose: : Lipoma arborescens (LA) is a benign intra‐articular lipomatous proliferation of the synovial membrane. This extremely rare condition has previously been treated by intra‐articular 90 Y radiosynoviorthesis but dosimetry literature on this form of radionuclide therapy is nonexistent. The authors detail methodology for successful treatment of LA and provide for the first time estimates of radiation dosimetry. The authors also analyze the biodistribution of the radiopharmaceutical over the course of the patientˈs treatment through sequential imaging. Methods: : A patient with bilateral LA underwent intracavity injection of 90 Y citrate colloid to the right and left knee joint spaces (181 and 198 MBq, respectively). SPECT/CT datasets were acquired over 9 days to quantify the biodistribution and kinetics of the radiopharmaceutical. Radiation dosimetry was performed using the MIRD schema (through OLINDA software), a custom voxel‐based method, and a direct Monte Carlo calculation (OEDIPE). Results: : Follow‐up MRI showed marked reduction in LA size in both knees. Mean absorbed doses to the LA were 21.2 ± 0.8 and 42.9 ± 2.3 Gy using OLINDA, 8.1 ± 0.3 and 16.7 ± 0.5 Gy using voxel based methodology, and 8.2 ± 0.3 and 15.7 ± 0.5 Gy for OEDIPE in the right and left LA, respectively. Distribution of the radiopharmaceutical within the joint space alters over the imaging period, with less than 1% of the remaining activity having moved posteriorly in the knee cavity. No uptake was detected outside of the joint space after assessment with whole‐body scintigraphy. Conclusions: : An activity of approximately 185 MBq successfully relieved clinical symptoms of LA. There was good correlation between direct Monte Carlo and voxel based techniques, but OLINDA was shown to overestimate the absorbed dose to the tumor. Accurate dosimetry may help select an activity more tailored to the specific size and location of the LA.